PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (TCL) UNTUK MENINGKATKAN HASIL BELAJAR MATERI PENGADAAN BIBIT TERNAK RUMINANSIA PERAH KELAS XI ATR 1 SMKN 1 CANGKRINGAN - BETTY MAYASARI (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2022)
This study aims to improve student learning outcomes by using the Contextual Teaching and Learning (CTL) learning model material for the Procurement of Dairy Ruminants for Students XI ATR 1 at SMK N 1 Cangkringan in the 2021/2022 academic year. This research was conducted from July to October 2021. The subjects of the class action research were students of class XI ATR 1 SMK Negeri 1 Cangkringan in the 2021/2022 academic year, totaling 34 students. In this classroom action research data collection using tests and observations. From the results of the study obtained data on improving student learning outcomes. This research was carried out with actions carried out with research steps that had been planned, namely by first compiling a lesson plan containing the steps for implementing the CTL learning model which had to fulfill seven 7 important elements, namely: inquiry, questioning (questioning), constructivism (constructivism), modeling learning community (learning community), authentic assessment (authentic assessment) and reflection (reflection) in the implementation of learning. The next step is in the form of data collection which is carried out by conducting observations and tests. After the data was obtained, reflection was carried out and carried out a report on the results of the research. The results of the application of the Contextual Teaching Learning (CTL) learning model can improve learning outcomes for Dairy Ruminant Agribusiness subjects on dairy ruminant seed material in class X ATR 1 students at SMK N 1 Cangkringan, this is evidenced by the increase in the average value of learning outcomes, namely the cycle 1 the average value of class learning outcomes is 71.91 in cycle 2 the average value of learning outcomes is 87.06, an increase of 15.15. Thus it can be concluded that the application of the Contextual Teaching and Learning (CTL) learning model can improve learning outcomes of Dairy Ruminant Agribusiness Materials for Procurement of Livestock Seeds in class X ATR 2 SMK Negeri 1 Cangkringan. ABSTRAKPenelitian ini bertujuan untuk miningkatkan hasil belajar siswa dengan menggunakan model pembelajaran Contextual Teaching And Learning (CTL) materi Pengadaan Bibit Ternak Ruminansia Perah pada Siswa XI ATR 1 di SMK N 1 Cangkringan Tahun Pelajaran 2021/2022. Penelitian ini dilaksanakan pada bulan Juli sampai dengan bulan Oktober tahun 2021. Subyek penelitian tindakan kelas adalah peserta didik kelas XI ATR 1 SMK Negeri 1 Cangkringan tahun pelajaran 2021/2022 yang berjumlah 34 orang siswa. Dalam penelitian tindakan kelas ini pengambilan datanya menggunakan tes dan observasi. Dari hasil penelitian diperoleh data peningkatan hasil belajar siswa. Penelitian ini dilakukan dengan tindakan yang dilaksanakan dengan langkah-langkah penelitian yang telah direncanakan, yaitu dengan terlebih dahulu menyusun RPP berisi langkah-langkah penerapan model pembelajaran CTL yang harus memenuhi tujuh 7 elemen penting yaitu : inkuiri, pertanyaan (questioning), konstruktivistik (constructivism), pemodelan (modelling) masyarakat belajar (learning community) penilaian otentik (authentic assesement) dan refleksi (reflection) dalam pelaksanaan pembelajaran. Langkah selanjutnya adalah berupa pengumpulan data yang dilaksanakan dengan melakukan observasi maupun tes. Setelah data diperoleh kemudian dilakukan refleksi dan melakukan laporan hasil penelitian. Hasil penerapan model pembelajaran Contextual Teaching Learning (CTL) dapat meningkatkan hasil belajar mata pelajaran Agribisnis Ternak Ruminansia Perah pada materi bibit ternak ruminansia perah pada siswa kelas X ATR 1 di SMK N 1 Cangkringan hal ini dibuktikan dengan meningkatnya nilai rata rata hasil belajar yaitu pada siklus 1 nilai rata rata hasil belajar kelas adalah 71,91 pada siklus 2 nilai rata rata hasil belajar adalah 87,06 terjadi peningkatan sebesar 15,15. Dengan demikian dapat disimpulkan bahwa penerapan model pembelajaran Contextual Teaching and Learning (CTL) dapat meningkatkan hasil belajar Agribisnis Ternak Ruminansia Perah Materi Pengadaan Bibit Ternak pada kelas X ATR 2 SMK Negeri 1 Cangkringan.